2020
DOI: 10.3390/su12114506
|View full text |Cite
|
Sign up to set email alerts
|

Coercive, Normative and Mimetic Pressures as Drivers of Environmental Management Accounting Adoption

Abstract: This paper explores the impact of institutional pressures on the adoption of environmental management accounting (EMA). EMA has been recognized as a valuable mechanism to deal with environmental issues. This paper uses institutional theory to explain the drivers of EMA adoption in Pakistan. Data were collected from the manufacturing sector in Pakistan through a questionnaire-based survey. The study concludes that coercive, normative and mimetic pressures have a significant and positive impact on the adoption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
144
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(164 citation statements)
references
References 50 publications
17
144
2
1
Order By: Relevance
“…The absence of the importance of customers', activists', and media concern (and public awareness in general) while the significance of regulation pressures appear to be a contradicting result as the voice of government is believed to be the voice of the general public. The result related to regulatory bodies' concern is consistent with another recent study on institutional pressures and corporate environmental responsiveness from Pakistan which has also found coercive pressure (pressures from regulatory bodies) as an indicator corporate environmental responsibility [79]. Similarly, Shin et al [80] also found government involvement as a positive indicator for corporate social responsibility activities by Indian firms, and Park and Choi [77] found government as a major factor in promoting local CSR activities of multinational firms operating in Korea.…”
Section: Discussionsupporting
confidence: 84%
“…The absence of the importance of customers', activists', and media concern (and public awareness in general) while the significance of regulation pressures appear to be a contradicting result as the voice of government is believed to be the voice of the general public. The result related to regulatory bodies' concern is consistent with another recent study on institutional pressures and corporate environmental responsiveness from Pakistan which has also found coercive pressure (pressures from regulatory bodies) as an indicator corporate environmental responsibility [79]. Similarly, Shin et al [80] also found government involvement as a positive indicator for corporate social responsibility activities by Indian firms, and Park and Choi [77] found government as a major factor in promoting local CSR activities of multinational firms operating in Korea.…”
Section: Discussionsupporting
confidence: 84%
“…Researchers use isomorphic pressures to differentiate forces and establish particular characteristics related to their use and implementation ( Kummer et al., 2020 ). This isomorphism can be divided into three parts within the institutional theory: coercive, normative, and mimetic pressures ( Latif et al., 2020 ). We discuss how these influence digitization of MSEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of three institutional pressures related to coercion, normative, and mimetic isomorphic forces, companies are able to ensure legitimacy (Kolk and Perego, 2010;Mart ınez-Ferrero and Garc ıa-S anchez, 2017). Therefore, institutional pressures are different in nature and can be divided into coercion, normative, and mimetic pressures (Latif et al, 2020). It is believed that coercive pressure mainly comes from political influence and an organization's need for legitimacy, such as implemented regulations or laws or dependence on other organizations.…”
Section: Conceptual Research Modelmentioning
confidence: 99%